PIM2 inhibition promotes MCL1 dependency in plasma cells involving integrated stress response-driven NOXA expression - Marion Haas; Sabrina Cherfa; Léa Nguyen; Maxence Bourgoin; Gersende Caron; Elise Dessauge; Tony Marchand; Laurent Delpy; Patrick Auberger; Jérôme Moreaux; Arnaud Jacquel; Thierry Fest (Nature Communications)
Abstract Our study explores the complex dynamics of the integrated stress response (ISR) axis, highlighting PIM2 kinase’s critical role and its interaction with the BCL2 protein family, uncovering key mechanisms of cell survival and tumor progression. Elevated PIM2 expression, a marker of various cancers, often correlates with disease aggressiveness. Using a model of normal and malignant plasma cells, we show that inhibiting PIM2 kinase inhibits phosphorylated BAD production and activates ISR-mediated NOXA expression. This shift towards MCL1 dependence underscores the synergy achieved through combined PIM/MCL1 inhibition, driven largely by ISR-mediated NOXA expression. In mouse xenograft models, dual targeting of PIM2 and MCL1 effectively controls tumor growth—a response reversed by ISR-specific inhibition and upregulation of genes linked to tumor cell dissemination. This work elucidates the molecular intricacies of PIM2 inhibition and its implications for cancer therapy, especially in tumors with elevated PIM2 expression.